Analisis Perilaku Keuangan Mahasiswa Vokasi Akuntansi di Yogyakarta - Sriniyati Sriniyati; Erlinda Nur Khasanah (Jurnal Akuntansi dan Pajak, 2023)
The purpose of this study was to examine the effect of financial literacy, academic ability, and gender of accounting vocational students’s financial behavior. The data used in this research was primary data collected by distributing questionnaires to students majoring in accounting at Vocational Colleges in Special Region of Yogyakarta (DIY). The samples consisted of 223 samples. To test the hypotheses, this study used multiple regression analysis through the SPSS version 26 program. The results of this study indicated that financial literacy and academic ability had a positive and significant effects on financial behavior. Meanwhile, gender had no effect on financial behavior.